Kesehatan reproduksi dan keluarga berencana: implikasi program aksi Kairo di Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Abstract Cairo action program or more popularly known as "Plan of Action" is not a difficult thing to be done in Indonesia provided that it relates to the mandate of GBHN (Guidelines of State Policy) 1993 and of Act Number 10 1992 as well as is not against the main point of the Second PIP (Long-Term Development), i.e. the economic field is in line with the quality of human resources. In this writing, the State Minister on Population/Head of BKKBN (National Family Planning Board) gives some explanation about the "Plan of Action" among other things: reproduction rights, reproduction health, and family planning. Most of these things have been done in Indonesia. Therefore, it was not surprising if Indonesia gave more inputs in the Cairo conference.